Pengembangan Sistem Marketplace Kadin Kota Batu Menggunakan Metode Incremental - Istar Hamal Haris (Jurnal Repositor, 2023)
The research problem is the Koperasi Mikawa which is one of the business entities of the Batu City's Kadin wants to provide a online marketplace as a marketing platform for UMKM products, because so far the product sales and promotion has been done manually, so buyers can access the products they are looking for. In the case study that we did on the object of this research, it did not take too long to develop the system, so it was appropriate to use the incremental method because this method is suitable for developing systems that are not too large and can be done in a short time, the development of this system uses the Codeigniter framework by using PHP and MySQL programming languages. Based on testing using the incremental method, it can be seen that Kadin Kota Batu’s marketplace is well received with an average SUS score of "80" indicating that the Adjective Rating is in the "Excellent" category with a Grade Scale of "B" and an Acceptability rating of high marginal with status "Acceptable".